Timing of imagery rescripting during schema therapy for borderline personality disorder: the LUCY trial - Koppeschaar, Annemieke; Bachrach, Nathan; Arntz, Arnoud (Frontiers in Psychiatry, 2023)
Early childhood adversity plays an important role in the etiology of Borderline Personality Disorder (BPD). Current evidence suggests that trauma treatment for patients with BPD can be performed safely and that early trauma treatment has a positive effect on the course of PD.However, there is a scarcity of RCTs comparing the effects of the timing of trauma treatment during ST for BPD on BPD Severity. Therefore, the LUCY trial investigates the effects of the timing of trauma treatment by comparing early trauma treatment using Imagery Rescripting (ImRs) on the course of BPD during Schema Therapy (ST) to trauma treatment in the middle of the treatment course.In this multicenter RCT two conditions are compared among 73 individuals with BPD. The participants receive combined individual and group ST in both conditions. However, in condition (A), participants directly start ImRs in the individual sessions, in months 2-4; and in condition (B), participants receive ST-as-Usual (STAU), in which ImRs is not allowed during months 2-4. Treatment follows ST treatment protocols and consists of a fixed combination of individual sessions and group sessions with a maximum of nine patients, and has a maximum duration of 25 months. The primary outcome is change in BPD severity, which is assessed with the Borderline Personality Disorder Severity Index-5 by independent raters blinded to treatment. Secondary outcome measures include treatment retention, disconnection/rejection schemas, general functioning, posttraumatic stress disorder symptoms, general psychopathological complaints, quality of life, happiness, schemas, and schema modes.Multilevel analysis will be performed to analyze and compare changes in BPD severity between conditions as well as generalized linear mixed model analyses to test predictors and moderators.This study will increase the knowledge on whether trauma treatment early in therapy positively affects the course of BPD manifestations during ST. When the early application of ImRs leads to a faster decrease in BPD manifestations, the treatment of BPD patients might be shortened, leading to improved treatment outcomes and decreased healthcare expenses.Moreover, sub-studies will expand our knowledge of how ST works and the factors that influence the outcome of treatment.